2008
DOI: 10.1002/bem.20456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gestational exposure to 1.95‐GHz W‐CDMA signals for IMT‐2000 cellular phones: Lack of embryotoxicity and teratogenicity in rats

Abstract: The present study was designed to evaluate whether gestational exposure to an EMF targeting the head region, similar to that from cellular phones, might affect embryogenesis in rats. A 1.95-GHz wide-band code division multiple access (W-CDMA) signal, which is one applied for the International Mobile Telecommunication 2000 (IMT-2000) system and used for the freedom of mobile multimedia access (FOMA), was employed for exposure to the heads of four groups of pregnant CD(SD) IGS rats (20 per group) for gestational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 16 publications
2
17
2
2
Order By: Relevance
“…The study results conflict with [25,26], who discovered that prenatal exposure of rats to 915-MHz microwave radiation did not induce or exhibit teratogenic effects on the foetal skeleton. Nishimura et al [27] found that exposure to intermediate frequency (300 Hz-100 KHz) magnetic fields during embryogenesis showed no teratogenic effect under experimental conditions.…”
Section: Discussioncontrasting
confidence: 98%
“…The study results conflict with [25,26], who discovered that prenatal exposure of rats to 915-MHz microwave radiation did not induce or exhibit teratogenic effects on the foetal skeleton. Nishimura et al [27] found that exposure to intermediate frequency (300 Hz-100 KHz) magnetic fields during embryogenesis showed no teratogenic effect under experimental conditions.…”
Section: Discussioncontrasting
confidence: 98%
“…Moreover, the results of yet another study (7) showed that a 2 h per day, 7 day a week, exposure of rats to 900 MHz radiation over ten months did not activate testes caspase-3, a well-known feature of typical apoptosis. Ogawa et al (26) and Sommer et al (27) studied four generations of exposed rats and found no negative effect. Lee et al (28) also did not fi nd any effects on rat spermatogenesis after simultaneously combined Code Division Multiple Access (CDMA) and Wideband Code Division Multiple Access (WCDMA) exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Lee et al, 2009;Ogawa et al, 2009;Sommer et al, 2009) found no harmful effects of exposure on the fertility and development of the animals. However, a study of the effects of exposure of young animals (Kumlin et al, 2007) found a slight improvement in one of several measures of adult behavioural performance.…”
Section: Animal Studiesmentioning
confidence: 96%